Isotopic fractionation during acid digestion of calcite: A combined ab initio quantum chemical simulation and experimental study. (25th May 2020) - Pramanik, Chirantan; Chatterjee, Swastika; Fosu, Benjamin R.; Ghosh, Prosenjit
Abstract : Rationale: Carbonate clumped isotope analysis involves the reaction of carbonate minerals with phosphoric acid to release CO2 for measurement in a gas‐source isotope ratio mass spectrometer. Although the clumped isotope proxy is based on the temperature dependence of 13 C– 18 O bonding preference in the mineral lattice, which is captured in the product CO2, there is limited information on the phosphoric acid reaction mechanism and the magnitude of clumped isotopic fractionation (mass 63 in CO3 2− to mass 47 in CO2 ) during the acid digestion. Methods: We studied the reaction mechanism for the phosphoric acid digestion of calcite using first‐principles density functional theory. We identified the transition state structures for each reaction involving different isotopologues and used the corresponding vibrational frequencies in reduced partition function theory to estimate the Δ 47 acid fractionation. Experimental Δ 47 data were acquired by processing the sample CO2 gas through the dual‐inlet peripheral of a ThermoFinnigan MAT253 isotope ratio mass spectrometer. Results: We showed that the acid digestion reaction, which results in the formation of CO2 enriched with 13 C– 18 O bonds, began with the protonation of calcium carbonate in the presence of water. Our simulations yielded a relationship between the Δ47 acid fractionation and reaction temperature as Δ47 = −0.30175 + 0.57700 × (10 5 / T 2 ) – 0.10791 × (10 5 / T 2 ) 2, with T varying between 298.15 and 383.15 K. Conclusions: We propose a reaction mechanism that shows a higher slope (Δ47 acid fractionation vs. 1/ T 2 curve) for the phosphoric acid digestion of calcite than in previous studies. The theoretical estimates from the present and earlier studies encapsulate experimental observations from both "sealed vessel" and "common acid bath" acid digestion methods.